2019
DOI: 10.1590/1519-6984.187647
|View full text |Cite
|
Sign up to set email alerts
|

Study on assessment of proximate composition and meat quality of fresh and stored Clarias gariepinus and Cyprinus carpio

Abstract: The organoleptic evaluation and proximate analysis of Clarias gariepinus and Cyprinus carpio were determined in fresh fish and when refrigerated at two different temperatures (-21 °C and 4 °C) for a period of six weeks. A panel of twelve trained judges evaluated the color (live), texture, softness and flavor of fish meat after two minutes’ steam cooking. Average score revealed a general decline in organoleptic properties such as color, texture, freshness, and taste of C. gariepinus and C. carpio stored at two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
7
6
0
Order By: Relevance
“…(Tables 1-2). Mahaboob et al (2018) had found a decreased amount of moisture and a high amount of protein and fat content in the fried stage than the raw stage, closely similar to the present findings.…”
Section: Resultssupporting
confidence: 91%
“…(Tables 1-2). Mahaboob et al (2018) had found a decreased amount of moisture and a high amount of protein and fat content in the fried stage than the raw stage, closely similar to the present findings.…”
Section: Resultssupporting
confidence: 91%
“…Scanty of work available on body composition on freshwater sh exposed to BPA In the present study lipid contents of sh decreased at a higher concentration of bisphenol A. Previously, similar reports available on C. gariepinus (Mahboob et al, 2018), Tilapia (Sana et al, 2017) exposed to toxicants. Presently moisture contents were also decreased like protein and lipid contents in sh exposed to bisphenol-A.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, it was observed that the moisture content of the wild fish decreased with increasing body weight with the small catfish and tilapia reporting 72.4 % and 73.1 %, respectively while the large catfish and tilapia having 70.9 % and 71.2 %, respectively. Since feeding system A had higher dietary protein, the findings of the present study concur with other studies which reported that in fish muscle, moisture and ash contents decrease with an increase in fats and protein contents and vice versa (Mahboob, Al-Ghanim, Al-Balawi, Al-Misned, & Ahmed, 2019;Jim, Garamumhango & Musara, 2017) and that increased water content is due to decreasing fat and protein contents in the fish body (Mahboob et al, 2019;Jim et al, 2017). The lower moisture content in wild fish may additionally be attributed to more physical efforts performed by the wild fish species to capture food organisms in the natural habitat than the farmed fish which has plenty of food supply in the ponds (Jim et al, 2017).…”
Section: Proximate Compositionsupporting
confidence: 92%